2012
DOI: 10.7314/apjcp.2012.13.3.1011
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Use does not Discourage Adolescent Smoking in Japan

Abstract: Objective: The possibility that smoking prevalence among junior and senior high school students may decrease with increasing mobile phone bill was reported by the mass media in Japan. We conducted a nationwide survey on adolescent smoking and mobile phone use in Japan in order to assess the hypothesis that mobile phone use has replaced smoking. Methods: A total of 70 junior high schools (response rate; 71%), and 69 high schools (90%) from all over Japan responded to 2005 survey. Students in the responding scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…EMC explained unique substance use variance over and beyond FTF interactions and average classroom substance use. These findings are consistent with previous research positively linking EMC to adolescent substance use (e.g., Leena et al 2005;Ohannessian 2009;Osaki et al 2012). Further, EMC strengthened the positive associations of FTF interactions after school with tobacco use, FTF interactions in the evening with tobacco and cannabis use, and average classroom alcohol use with individual alcohol use.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…EMC explained unique substance use variance over and beyond FTF interactions and average classroom substance use. These findings are consistent with previous research positively linking EMC to adolescent substance use (e.g., Leena et al 2005;Ohannessian 2009;Osaki et al 2012). Further, EMC strengthened the positive associations of FTF interactions after school with tobacco use, FTF interactions in the evening with tobacco and cannabis use, and average classroom alcohol use with individual alcohol use.…”
Section: Discussionsupporting
confidence: 91%
“…First, due to the cross-sectional and correlational design, no causal inferences can be made. It may be that adolescents who are already at risk for substance use are also at risk for higher levels of EMC (Leena et al 2005;Osaki et al 2012), or it may be that adolescents with high levels of substance use are more drawn to EMC because their substance use enhances their social connectedness and standing among peers (Killeya-Jones et al 2007). Further, it may be that adolescents specifically select peers who already have similar levels of substance use to communicate with via EMC (Stoddard et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, due to the repeated cross-sectional design, no causal inferences can be made. Adolescents who are at risk of substance use may also be at risk of higher levels of EMC (Osaki et al 2012 ), or adolescents who use substances use may be more drawn to EMC because their substance use enhances their social connectedness and standing among peers (Killeya-Jones et al 2007 ). Second, although we included an important set of social and individual factors in our models and showed that they contributed to substance use independently, a more elaborate model of substance use should also include biological, genetic and personality factors, as well as their interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier people start smoking (eg, early teenage), the greater the harm. Although the smoking rates of junior-high-school students have been rapidly declining in Japan in the past 20 years, 29 we need to prevent smoking in junior high school. In the USA 2013 Youth Risk Behavior Survey, the prevalence of current cigarette smoking was 10.2% among ninth graders.…”
Section: Discussionmentioning
confidence: 99%